Rehabilitation Enablement in Chronic Heart Failure—a facilitated self-care rehabilitation intervention in patients with heart failure with preserved ejection fraction (REACH-HFpEF) and their caregivers: rationale and protocol for a single-centre pilot randomised controlled trial. Issue 10 (25th October 2016) - Eyre, V; Lang, C C; Smith, K; Jolly, K; Davis, R; Hayward, C; Wingham, J; Abraham, C; Green, C; Warren, F C; Britten, N; Greaves, C J; et al.
Abstract : Introduction: The Rehabilitation EnAblement in CHronic Heart Failure in patients with Heart Failure (HF) with preserved ejection fraction (REACH-HFpEF) pilot trial is part of a research programme designed to develop and evaluate a facilitated, home-based, self-help rehabilitation intervention to improve self-care and quality of life (QoL) in heart failure patients and their caregivers. We will assess the feasibility of a definitive trial of the REACH-HF intervention in patients with HFpEF and their caregivers. The impact of the REACH-HF intervention on echocardiographic outcomes and bloodborne biomarkers will also be assessed. Methods and analysis: A single-centre parallel two-group randomised controlled trial (RCT) with 1:1 individual allocation to the REACH-HF intervention plus usual care (intervention) or usual care alone (control) in 50 HFpEF patients and their caregivers. The REACH-HF intervention comprises a REACH-HF manual with supplementary tools, delivered by trained facilitators over 12 weeks. A mixed methods approach will be used to assess estimation of recruitment and retention rates; fidelity of REACH-HF manual delivery; identification of barriers to participation and adherence to the intervention and study protocol; feasibility of data collection and outcome burden. We will assess the variance in study outcomes to inform a definitive study sample size and assess methods for the collection of resource use and intervention delivery cost data to develop the cost-effectiveness analyses framework for any future trial. Patient outcomes collected at baseline, 4 and 6 months include QoL, psychological well-being, exercise capacity, physical activity and HF-related hospitalisation. Caregiver outcomes will also be assessed, and a substudy will evaluate impact of the REACH-HF manual on resting global cardiovascular function and bloodborne biomarkers in HFpEF patients. Ethics and dissemination: The study is approved by the East of Scotland Research Ethics Service (Ref: 15/ES/0036). Findings will be disseminated via journals and presentations to clinicians, commissioners and service users. Trial registration number: ISRCTN78539530 ; Pre-results .